SEARCH FOR EXCITED CHARGED LEPTONS IN Z0 DECAYS - Abreu, P; Adam, W; Adami, F; Adye, T; Akesson, T; Alekseev, G; Allen, P; Almehed, S; Alted, F; Alvsvaag, S; Amaldi, U; Anassontzis, E; et al. (1992)
Using a data sample of 115000 hadronic Z0 decays, a search was performed for the production of excited charged leptons decaying into an ordinary lepton and one photon. Pair production of excited leptons of mass below 45 GeV/c2 is excluded. From an analysis of the lepton-photon mass spectra this experiment is also able to exclude single production of these particles for masses that reach up to 85 GeV/c2, if the compositeness scale is below 1 TeV. © 1992 Springer-Verlag.